Floristic composition, horizontal structure and conservation potential of trees and shrubs on Isla del Caño, Biological Reserve, Costa Rica - Oviedo Pérez, Paul (2020)
The objective of this study was to analyze the floristic composition, the horizontal structure and the conservation potential of trees and shrubs on Isla del Caño, Costa Rica. Two sites with different stages of succession (slope and plain) were selected. At each site, seven plots were established (10 m x 30 m) and an inventory was made of all trees with a diameter ≥ 10 cm. In the center of each plot a quadrant of 5 m x 5 m was delimited and shrubs and trees with a diameter smaller than 10 cm were identified. The composition was analyzed from the registered species and the number of individuals per species. The horizontal structure was analyzed using the tree density, the importance value index (IVI) and the distribution by diametric class as parameters. The species identified were assigned to a conservation priority: urgent, high, medium, low. The results indicated a significant difference in the composition between both sites. The ecological weight falls on the species Brosimum utile and Ocotea insularis. Both species were concentrated in the plain; while the vegetation of the slope was constituted by heliophyte species. The percentage of similarity between canopy and understory species was 17% for the slope and 36% for the plain. Regeneration of the canopy species was abundant, mainly for B. utile. The distribution of the trees by diametric classes showed the inverted "J" shape. Most species were assigned to a low conservation category. This study confirms that few species had high dominance and abundance, possibly as a response of the species to the environmental conditions of the island. The abundance of trees and shrubs important for restoration; as well as, the timber species, justify the conservation of the island.